Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T17:15:08+01:00
A) 2x -(-4-3x)= 2x +4 +3x= 5x+4

b) 10-2(t+1) = 10- 2t +10 = 20 -2t
c) -3 (2y +jedna trzecia) +4y = -6y -1 +4y = -2y -1 = -(2+1)
d) -6y(1-0,5u) + trzy u drugich = -6y +3u + 3u/2 =-6y +4,5u
e) 2(3w-1)- w+2drugich= 6w -2 -w/2 +1 = 5,5w+1
f) 3(a-2b)-5(b-2a) = 3a -6b -6b +10a = 13a -12b
13 3 13
2010-02-04T17:15:41+01:00
A) 2x -(-4-3x)
2x+4+3x
5x+4
b) 10-2(t+1)
10-2t-2
8-2t
c) -3 (2y +jedna trzecia) +4y
-6y-1+4y
-2y-1
d) -6y(1-0,5u) + trzy u drugich
-6y+3yu+trzy u drugich
e) 2(3w-1)- w+2drugich
6w-2-w+dwie drugie?
5w
f) 3(a-2b)-5(b-2a)
3a-6b-5b+10a
13a-11b
9 2 9
  • Użytkownik Zadane
2010-02-04T17:15:54+01:00
A) 2x -(-4-3x)= 2x+4+3x =5x+4
b) 10-2(t+1)= 10-2t-2 = 8 -2t
c) -3 (2y +jedna trzecia) +4y = -6y - 1 +4y = 10y -1
d) -6y(1-0,5u) + trzy u drugich = -6y +3yu + 3 u drugich
e) 2(3w-1)- w+2drugich = 6w -2 -w + 1 (bo dwie drugich to 1 ) = 5w -1
f) 3(a-2b)-5(b-2a) = 3a -6b -5b + 10a = 13a - 11b
8 4 8